Knowledge on Children’s Attention Deficit Hyperactivity Disorder among School Teachers in Chitwan - Lamichhane, S; Sharma, P (Journal of Manmohan Memorial Institute of Health Sciences, 2019)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most common psychiatric disorders in children and adolescents. Children with ADHD are at risk for psychological, social and academic problems so that teacher’s knowledge on ADHD affects the child’s academic and psychological difficulties. Objective of this study was to identify the knowledge about ADHD in children among school teachers and identify association between knowledge and selected variables. Methods: We used descriptive and cross sectional research design. Structured self administered questionnaire was used to collect data. Total 9public and private schools wererandomly selected for study. Calculated sample size was 380. However, 328 teachers returned the questionnaire (response rate was 86%). Collected data were entered in SPSS for analysis. Descriptive and inferential statistics were used for analysis of data. Results: Among 328 teachers, 68.3% had inadequate knowledge while 31.7% had adequate knowledge on ADHD. Age and years of teaching were significantly associated with knowledge of ADHD, however, sex of the teachers and type of school were not associated with knowledge of ADHD. Conclusion: Knowledge of ADHD among school teachers is still inadequate which suggests the need for effective health education programme on ADHD for understanding and managing the behavioural and psychological problems caused by ADHD among school children.